PELATIHAN: PEMBUATAN BANTEN ARI-ARI SEBAGAI MEDIA PENGUATAN PENDIDIKAN KARAKTER DAN PELESTARIAN TRADISI LOKAL - Desak Putu Saridewi; Ni Putu Ayu Budiartini (LP3M Universitas PGRI Mahadewa Indonesia, 2026)
The placenta burial tradition is one of the cultural practices in Hindu society that carries deep religious, social, and philosophical meanings. This study aims to examine the role of training in making banten ari-ari as a medium for strengthening character education based on local culture, as well as an effort to preserve tradition amid the currents of modernization. The method used is a descriptive qualitative approach through observation, discussion, and documentation techniques conducted during training activities among Hindu youth. The results show that the training in making banten not only improves participants’ technical skills but also enhances their understanding of the philosophical and symbolic values embedded in the placenta burial tradition, particularly those related to the concept of Catur Sanak and the implementation of Manusa Yadnya. In addition, the training process is able to internalize character values such as religiosity, responsibility, sincerity, and respect for life through direct experience. In the context of contemporary developments, this tradition remains relevant as a medium for character education; however, it requires adaptation to align with modern contexts without losing its essential values. Therefore, training in making banten ari-ari serves as an effective strategy for cultural preservation while simultaneously fostering the character development of young generations who are culturally grounded and spiritually aware.